Effect of doped-fiber's spooling on performance of S-band EDFA - Ahmad, Harith; Saat, Nor Kamilah; Harun, Sulaiman Wadi (John Wiley & Sons, 2005)
The effect of doped-fiber's spooling on performance of short wavelength band erbium-doped fiber amplifier (S-band EDFA) is demonstrated. Changing the spooling diameter resulted in a variation of gain and noise figure characteristics of this amplifier. The optimum spooling diameter is obtained in the range from 5 to 7 cm. Beyond this range, an inevitable degradation of gain and noise figure characteristics is observed due to the changes of phase matching wavelength. Therefore, maintaining the optimum spooling diameter is the important issue for the S-band EDFA.